PENGARUH HARGA, WORD OF MOUTH DAN KEBERAGAMAN PRODUK TERHADAP KEPUASAN KONSUMEN PADA TOKO MW DI CERMEE DENGAN KEPUTUSAN PEMBELIAN ULANG SEBAGAI VARIABEL INTERVENING - Febriyanto, Febriyanto; Tulhusnah, Lusiana; Sari, Rini Kartika (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The growth of the business world is very fast in line with the rapidly changing times, for example companies in the services and trade sectors. The establishment of many companies is a challenge for business actors, producers will be encouraged to innovate more creatively than other companies for the sustainability of their business. This research is explanatory research. The population in this research is MW Shop consumers. The sampling technique was determined by simple random sampling. Data analysis and hypothesis testing in this research used the Partial Least Square Structural Equation Model (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Price has a negative but not significant effect on repurchase decisions, Word of Mouth has a significant positive effect on repurchase decisions, Product diversity has a significant positive effect on repurchase decisions, Price has a negative but not significant effect significant effect on Consumer Satisfaction, Word of Mouth has a negative but not significant effect on Consumer Satisfaction, Product diversity does not have a significant positive effect on Consumer Satisfaction, Repurchase Decisions have a significant positive effect on Consumer Satisfaction. The results of the indirect influence hypothesis test show that the variable Price on consumer satisfaction through repurchase decisions has a negative but not significant effect, Word of Mouth on consumer satisfaction through repurchase decisions has a positive but not significant effect, Product diversity has a positive but not significant effect on consumer satisfaction through repurchase decisions. not significant.